Shale gas potential of the Lower Permian Gufeng Formation in the western area of the Lower Yangtze Platform, China. (November 2015) - Du, Xuebin; Song, Xiaodong; Zhang, Minqiang; Lu, Yongchao; Lu, Yangbo; Chen, Ping; Liu, Zhanhong; Yang, Shuai
Abstract: China is beginning to explore unconventional gas resources in the Lower Yangtze Platform. In the last two years, we conducted undiscovered hydrocarbon resource assessment to investigate the geological and geochemical characteristic of the Lower Permian Gufeng Formation, which is considered as one potential exploration layers in this area. Four outcrops and one well were used to determine the stratigraphic correlation, and 40 available samples were used for an analytical investigation. Because of continuous changes in the sedimentary environment, the "shale" of the Gufeng Formation not only includes black shale but also calcareous mudstone, silicalite, siliceous mudstone and carbonaceous shale. The thickness of the Gufeng Formation is between 0 m and 200 m, and it has two small depositional centers with an SW–NE strike on plane. The shale in the Gufeng Formation shows a high average TOC (total organic carbon) content of 3.41wt% (based on test of 40 samples), but the TOCs in different tract systems have significant differences (EHST-early highstand systems tract, average 9.85wt%; LHST-late highstand systems tract, average 0.96wt%; CS-condensed section, average 2.61wt%; TST-transgressive systems tract, average 0.76wt%). The shale is in the post-mature stage of thermal maturity (Tmax-temperature of maximum pyrolysis output = 339–518 °C) and is in the dry gas window of hydrocarbon generation (mean random vitrinite reflectance value, Ro = 1.24–1.99%). Clay minerals dominate the mineralogy followed by quartz minerals. Pyrite only is found in some samples of EHST, which is consistent with the presence of less anoxic conditions and lower levels of sediment dilution during sediment deposition. The EHST shale of the Gufeng Formation, which has a high content of organic carbon, tentatively could be regarded as a potential shale gas exploration target in this area. However, because the complex multistage tectonic background could have caused gas loss, the tectonic background and the hydrocarbon preservation condition must also be considered. Graphical abstract: Highlights: The first time to have a detailed discussion about the shale gas potential in the study area. The shale shows a high TOC, the post-mature stage of thermal maturity, the dry gas window. The EHST shale having high organic carbon is regarded as a potential shale gas exploration target.